THE CONTENTS OF SOME TRACE ELEMENTS IN THE AQUATIC ORGANISMS OF THE CASPIAN SEA - Vladimir A. Chaplygin; Tatiana S. Ershova; Vyacheslav F. Zaitsev (Юг России: экология, развитие)
Objective: to determine the levels of essential elements (copper, zinc and manganese) in the liver of Russian and Persian sturgeon and their basic food sites, as well as in the liver of the Caspian seal, which is a functional depot for many metals. Methods. Sampling was carried out according to generally accepted methods, determination of heavy metals produced by atomic-absorption spectroscopy using atomic absorption spectrometer with connection atomizaciej MGA-MD 915. Results. The concentration of zinc in all investigated sites exceed-valid, while zinc is not able to accumulate up the food chain. The level of accumulation of copper was higher than the maximum prescribed only in the liver of the Caspian seal as the holder of a faster metabolism. Manganese in maximum concentration has been found in the liver of the Caspian seal, but does not exceed the permissible values. Since the liver is the primary organ, concentrating this trace element. Conclusions. Accumulation of trace elements depends on the physiological characteristics of an organism, the properties of the trace element and from Wednesday.